PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DARMA PANCA SAMUDRA GRESIK - Muchammad Ramadhan Aris; Nur Cahyadi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research aims to determine the influence of work discipline and work environment on the performance employees of PT. Panca Samudra Gresik. This research is included in the category of causal associative research using a quantitative approach. The sampling technique uses saturated samples. The data analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that work discipline and work environment are proven to have a partially significant influence on employee performance at PT. Panca Samudra Gresik. These results can be interpreted that the existence of work discipline and work environment can improve employee performance at PT. Panca Samudra Gresik.